2022
DOI: 10.3390/nu14194039
|View full text |Cite
|
Sign up to set email alerts
|

Association of Coffee and Tea Consumption with the Risk of Asthma: A Prospective Cohort Study from the UK Biobank

Abstract: Background: Previous observational studies investigated the relationship between coffee and tea intake and the risk of asthma, however, the conclusions were inconsistent. Further, the combined effect of coffee and tea consumption on asthma has rarely been studied. Methods: We examined associations between the self-reported intake of tea and coffee and the risk of incident asthma in a total of 424,725 participants aged from 39 to 73 years old from the UK Biobank. Cox proportional hazards models were used to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…A study from South Korea found coffee intake had a protective effect on asthma (44). A prospective cohort study from the UK Biobank has found that coffee and tea intake may be protective against asthma (45). This study found coffee and tea intake were not associated with asthma.…”
Section: Discussionmentioning
confidence: 55%
“…A study from South Korea found coffee intake had a protective effect on asthma (44). A prospective cohort study from the UK Biobank has found that coffee and tea intake may be protective against asthma (45). This study found coffee and tea intake were not associated with asthma.…”
Section: Discussionmentioning
confidence: 55%
“…Fourth, we relaxed the p -value threshold ( p < 5 × 10 −6 ) of SNPs due to lack of sufficient SNPs (less than three) after linkage disequilibrium, resulting in the reduced robustness of MR results. Fifth, in the observational analyses, although exhaustive adjustment was conducted in the multivariable analyses, residuals or unmeasured confounders could not be excluded [ 49 , 50 , 51 ]. Finally, our analyses were limited to individuals of European ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…Gallocatechin has antioxidant functions and protective effects against diseases such as cancer and heart disease ( Someya et al, 2002 ). Caffeine relaxes smooth muscle of the bronchi, making it of value for the treatment of asthma and the bronchospasm of chronic bronchitis ( Lin et al, 2022 ). In addition, the various metabolites were predominantly enriched in metabolic pathways, secondary metabolite production, ABC transporters, D-amino acid metabolism, and other material metabolic activities after the inoculation with the “golden flower” fungi.…”
Section: Discussionmentioning
confidence: 99%